Body Mass Index Between 15 and 30 Does Not Influence Patient-Reported Outcomes After Anterior Cruciate Ligament Surgery Using a 10-mm-Diameter Bone-Tendon-Bone Graft - Mia Adler Lustig, B.S; Sean Hazzard, P.A., M.B.A; Brendan Fitzgerald, B.S; Nasir Stovall, B.S; Peter Asnis, M.D (Elsevier, 2024)
Purpose: To investigate the relation between body mass index (BMI) and outcomes after anterior cruciate ligament reconstruction (ACLR) using 10-mm-diameter bone-patellar tendon-bone grafts. Methods: In this retrospective study, the Surgical Outcome System was used to measure patient-reported outcomes before and after ACLR between 2015 and 2019. The inclusion criteria consisted on patients undergoing primary ACLR performed by the senior surgeon, with recorded age of 15 years or older and BMI of 15.0 to 30. The exclusion criteria included revisions, concomitant procedures, age younger than 15 years, and unknown BMI. Patients were divided into cohorts to evaluate the Marx Activity Rating Scale (MARS), Tegner, International Knee Documentation Committee (IKDC), and Lysholm scores at various time points from injury to 2 years postoperatively. Results: A total of 137 patients (100 male and 37 female patients) with an average age of 33 years (95% confidence interval, 30.6-35.4 years) and average BMI of 23.58 (95% confidence interval, 23.1-24.0) were divided into those with a BMI of 15 to 23.4 (group A, n = 69) and those with a BMI of 23.5 to 30 (group B, n = 68). A significant difference in MARS scores was found between the BMI groups before treatment, with mean scores of 11.55 (group A) and 9.41 (group B) (P = .011), and Tegner scores showed significance at 2 years, with scores of 6.45 and 5.41 for groups A and B, respectively (P = .009). Daily function scores were all insignificant. Female patients exhibited no significant differences across any patient-reported outcome measures or time points. Contrarily, male patients showed a significant difference in pretreatment MARS scores (14.30 in group A vs 9.96 in group B, P = .011). Additionally, scores at 2 years depicted Tegner values of 7.40 in group A versus 5.30 in group B (P = .012) and IKDC values of 96.92 in group A versus 90.47 in group B (P = .048). All results for female and male patients aged 30 years or younger indicated no significance. Conclusions: Regardless of patient age or sex, BMI is not significantly associated with patient-reported outcomes after ACLR using 10-mm-diameter bone-patellar tendon-bone grafts. Level of Evidence: Level III, retrospective cohort study.